(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
The regularities of the spatiotemporal distribution of the temperature in the winter period in the Ararat valley and the foothill zone have been discussed, analyzed and clarified. In the article, daily data of actual observations of the hydrometeorological service over the temperature of armospheric air during the winter period were used as the source material. It was found out that in the study area the tendency of increasing the average and extreme minimum values of air temperature over the winter period is predominantly observed. That is, in the region there is a softening of winters.